Qualitative selection of cuttings of Vanilla planifolia Andrews on the survival and morphogenetic development - Azofeifa-Bolaños, José Bernal; Rivera-Coto, German; Paniagua-Vásquez, Amelia; Cordero-Solórzano, Roberto (Agronomía Mesoamericana, 2018)
In Costa Rica, an urgent ex situ national conservation program for V. planifolia is needed due to the rarity, high risk of extinction in the wild and the economic importance; that places it, as the most profitable orchid worldwide. Due to the lack of research about wild species conservation and the importance to evaluate the agronomic performance of the wild-type relatives, as a strategy to increase the reduced genetic variability, the aim of this research was to evaluate the acclimatization capacity and morphogenetic performance of wild V. planifolia under nursery conditions. The effect of two treatments 1) qualitatively selected cuttings according to their phytosanitary quality, mechanical damage and vigorousness and 2) cuttings without selection, were evaluated. Some growth variables were evaluated: survival rate, weight, length, number of nodes of the new and original shoot; number and weight of the roots The survival of the selected cuttings was greater (60%) than those that were not (45%). The morphogenetic responses of the selected explants were statistically significant for all variables evaluated. This is the first time that an initial process of acclimatization and morphogenetic performance with a known genotype individual of V. planifolia, is reported under greenhouse condition, in Costa Rica. Therefore, it is the first attempt to the ex situ conservation of the species as a part of an integrated program focus on the in situ conservation in a systematic and sustainable way, as well as, the first values of the vigorousness to some growth variables out of natural conditions.